2022
DOI: 10.1007/jhep07(2022)018
|View full text |Cite
|
Sign up to set email alerts
|

Fermions in AdS and Gross-Neveu BCFT

Abstract: We study the boundary critical behavior of conformal field theories of interacting fermions in the Gross-Neveu universality class. By a Weyl transformation, the problem can be studied by placing the CFT in an anti de Sitter space background. After reviewing some aspects of free fermion theories in AdS, we use both large N methods and the epsilon expansion near 2 and 4 dimensions to study the conformal boundary conditions in the Gross-Neveu CFT. At large N and general dimension d, we find three distinct boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…The earliest example we found was from 35 years ago [15], where a free scalar field in three dimensions interacts via a classically marginal φ 4 coupling on a two dimensional boundary. More recent work utilizing and large N expansions to study boundary interactions includes [16][17][18][19][20][21].…”
Section: Jhep08(2022)282mentioning
confidence: 99%
“…The earliest example we found was from 35 years ago [15], where a free scalar field in three dimensions interacts via a classically marginal φ 4 coupling on a two dimensional boundary. More recent work utilizing and large N expansions to study boundary interactions includes [16][17][18][19][20][21].…”
Section: Jhep08(2022)282mentioning
confidence: 99%
“…To our knowledge, relatively little theoretical work has been done on critical fermionic systems with boundaries. While a recent tour-de-force calculation [20] computes critical exponents in the Yukawa model at fourth order in the epsilon expansion in the infinite system, the state of the art in the presence of a boundary is O( ) [21]. Refs.…”
Section: Jhep02(2023)129mentioning
confidence: 99%
“…Refs. [21,22] consider also the large N f limit. On the experimental side, the associated critical exponents have not yet been measured in the infinite system nor in the presence of a boundary, yet much promising work has been done to engineer graphene and graphene like systems which undergo this type of chiral symmetry breaking phase transition (see e.g.…”
Section: Jhep02(2023)129mentioning
confidence: 99%
“…In this section, we study the bulk-wedge two-point functions of scalar operators, and how they can be found from the Dyson-Schwinger (DS) equations up to O( ) with a quartic interaction in the bulk in d = 4 − , or a quartic boundary interaction in d = 3 − . This approach has been used in [63,64] in the context of a single boundary with a bulk interaction in d = 4 − . In a WCFT there are four OPE's in play: two for each boundary, which allow us to express bulk operators in terms of the boundary operators, and two more which express the boundary operators on the wall or the ramp in terms of edge operators.…”
Section: The Bulk-wedge Correlator From the Equation Of Motionmentioning
confidence: 99%